Good Palliative Care for a Patient with Schizophrenia Dying of Emphysema and Heart Failure - Griffith, Linda J. (Matrix Medical Communications, 2007)
Psychiatrists can offer much to the care of people who are chronically mentally ill and who are dying of a medical illness. In community psychiatry, the psychiatrist and other members of the treatment team often care for patients over many years, and gradually learn about patients' wishes and preferences, strengths and limitations, and areas of support and lack thereof. This database joins together with the psychiatrist's capacity for empathy to provide many of the necessary elements for palliative care during the final phases of these patients' lives. This composite case illustrates the treatment of a gentleman whose chronic schizophrenia was fairly well controlled until his pulmonary and cardiac disease began to progress rapidly.